Shifts in Middle School Students’ Environmentally Friendly Behaviors and Attitudes During the Covid-19 Pandemic in Turkey - Dilek Türkoğlu; Recep Bozyiğit; Esme Hacıeminoğlu (Jurnal Penelitian dan Pembelajaran IPA, 2026)
The study aimed to examine the eco-friendly behaviors and environmental attitudes exhibited by middle school students during the COVID-19 pandemic. This survey-based study compiles data collected from 191 middle school students across various regions of Turkey. Given the lockdown restrictions implemented due to the pandemic, the data was collected online by students who voluntarily set aside time to participate. The study utilized a survey focused on eco-friendly behaviors and attitudes. The findings reveal that middle school students demonstrated eco-friendly behaviors and held positive attitudes toward the environment. More than half of the students reported a change in their attitudes and behaviors toward the environment. This change was examined as part of the research, focusing on environmental protection, recycling, and other related topics. On the other hand, more than a quarter of the students reported no change in their relationship with the environment and noted that they had already adopted a positive and environmentally friendly attitude toward nature.